(untitled) (Research, Society and Development, 2022)
Rehabilitation of severely atrophic jaws has been a major problem for elderly patients and dentists. When conventional rehabilitation treatments are not possible, bone intervention is deemed necessary. Mandibles with less than 12 millimeters (mm) in height imply insufficient retention of the prosthesis, intolerance to mucosal load, pain and, consequently, incapacity of oral functions and decreased facial aesthetics. Endosseous implants are a widely accepted therapy for SRM rehabilitation, but it depends on the amount of bone available for a good prognosis. The Tent Pole technique is based on the addition of bone graft and expansion of the soft tissue matrix, mainly for cases of SRM with 6 mm or less of bone height available for rehabilitative treatments with endosseous dental implants. The objective of this report is to present and update a previously published clinical case of SRM reconstruction and rehabilitation using the tent pole technique, with 12 years of follow-up. The female patient, who underwent treatment at 63 years of age, received treatment using the Tent Pole surgical technique for mandibular reconstruction with cranial autogenous particulate bone graft. The treatment was favorable during the 12 years of control, the CT scan showed that the grafted bone was stable in volume and the mandible was enlarged in three dimensions.